A Study on Job Satisfaction among Engineers with Master’s Degree in Construction Management in Kathmandu Valley - Shrestha, Manjila; Bhattarai, Subash Kumar (International Journal on Engineering Technology and Infrastructure Development, 2024)
This study comprises of the assessment of level of job satisfaction of the engineers who hold a master’s degree in construction management in Kathmandu Valley by means of the Minnesota Satisfaction Questionnaire. The study population includes three engineering colleges in Kathmandu Valley. They are Nepal Engineering College (NEC), Institute of Engineering (IOE), Lumbini International Academy of Science and Technology (LIAST). 70 sample responses were received as primary data. Cronbach’s alpha was calculated by using SPSS and found to be 0.939. Engineers with master’s degree in construction management are highly satisfied with their job due to relation with co-workers with mean value of 3.94. This suggests that their colleagues' supportive behavior positively influences their work progress. In contrast, engineers are highly dissatisfied with the ‘Remuneration - My pay scale vs Job description’ as their value is below the acceptable level i.e. 2.74.